Comparing thermal comfort and air quality performance of two active chilled beam systems in an open-plan office. (March 2019) - Cehlin, Mathias; Karimipanah, Taghi; Larsson, Ulf; Ameen, Arman
Abstract: The traditional air distribution and supply devices in ventilated rooms are not always able to effectively remove excess heat from the space. Therefore, chilled beams, especially the active systems, are used to achieve the desired cooling demand. The focus of this paper was the potential benefit of a newly designed active chilled beam (ACB) system, to improve heat removal effectiveness local thermal condition and indoor air quality in the occupants' breathing zone. The system based on 1-way flow design (1W-ACB) was installed in an open-plan office and its performance was studied by analysing the temperatures, velocities and tracer gas concentrations in predetermined risky zones. The system was compared against a traditional 4-way flow design (4W-ACB). The obtained results showed that heat removal effectiveness was slightly higher for the 1W-ACB system compared to the 4W-ACB system. The local thermal condition was very good close to the workstations when using 1W-ACB. The benefits of the new system were also shown in the occupied zone by analysing the mean age of air and air-change effectiveness (ACE) in the breathing level at the workstation locations. The 1W-ACB system provided air with lower mean age (fresher air), and therefore higher ACE, near the breathing zone at the workstations compared to the 4W-ACB. On the other hand, the 4W-ACB system had the advantage of providing high thermal and mean age of air uniformity throughout the room. Highlights: Unique design of an active chilled beam system based on 1-way flow. Comparative study between 1-way flow system and traditional 4-way flow system. The new system can provide better indoor climate than traditional system. Risk of draught problems at ankle level in 1-way flow system.